Exploring the Educational Potential of VR: Immersive vs. Non-Immersive VR in Virtual Space Learning - Delvita Santy (Universitas Atma Jaya Yogyakarta, 2025)
This study explores the impact of Virtual Reality (VR) in architectural education at Atma Jaya Yogyakarta University, focusing on the differences between immersive and non-immersive VR experiences. Two groups of architecture students participated in the study: one group used VR headsets, while the other engaged with non-immersive virtual environments. Both groups completed a User Experience Questionnaire (UEQ), and their responses were analysed using the Mann-Whitney U test. The study found that students using VR headsets reported significantly higher engagement, satisfaction, and overall positive experience than non-immersive methods. These findings suggest that immersive VR has more potential to enhance student learning experiences in architectural education, providing valuable insights for developing practical digital learning tools and strategies.